Modulação fase e frequência das oscilações neurais na atividade epileptiforme de camundongos neonatos infectados pelo Zika virus - Pinheiro, Daniel Jose Lins Leal [UNIFESP] (2019)
Modulation of brain activity is one of the main mechanisms capable of demonstrating the synchronization dynamics of neural oscillations. In epilepsy, modulation is a key concept as seizures are essentially resulting from hypersynchronization and hyperexcitability of neurons. In this study, we have introduced a time-dependent index based on the Kullback-Leibler divergence to quantify the effects of modulations in the phase and frequency of neural oscillations in mice exhibiting epileptiform activity induced by the neonatal Zika virus (ZIKV) infection. We demonstrate that fast oscillations (gamma and beta 2) are the most modulated waves in terms of phase, during seizures, whereas slow waves (delta and theta) mainly undergo changes in frequency. Moreover, other brain rhythms show different extents of frequency modulation in ZIKV-infected mice compared to the control group. Furthermore, the use of this novel index allowed detection of specific patterns associated with the interdependent modulation of phase and frequency in neural activity. These findings instigate new studies on the effects of ZIKV infection on neuronal networks from epileptiform electrophysiological activities.